THE MODULE «VIRTUAL ELECTRONIC BOARD» OF DISTANCE LEARNING SYSTEM «KHERSON VIRTUAL UNIVERSITY 2.0» - Kozlovskij, Є.О.; Ljakutin, B.B.; Kravtsov, Г.М. (Journal of Information Technologies in Education (ITE), 2010)
Results of structure modeling, construction of learning model and development of program module Whiteboard – a virtual electronic board of distance learning system «Kherson Virtual University» are presented.